Permeability of Bituminous Coal to CH4 and CO2 Under Fixed Volume and Fixed Stress Boundary Conditions: Effects of Sorption - Liu, Jinfeng; Spiers, Christopher J. (Frontiers in Earth Science, 2022)
Permeability evolution in coal reservoirs during CO2-enhanced coalbed methane (ECBM) production is strongly influenced by swelling/shrinkage effects related to sorption and desorption of CO2 and CH4, respectively. Recent research has demonstrated fully coupled stress–strain–sorption–diffusion behavior in small samples of cleat-free coal matrix material exposed to a sorbing gas. However, it is unclear how such effects influence permeability evolution at the scale of a cleated coal seam and whether a simple fracture permeability model, such as the Walsh elastic asperity loading model, is appropriate. In this study, we performed steady-state permeability measurements, to CH4 and CO2, on a cylindrical sample of highly volatile bituminous coal (25 mm in diameter) with a clearly visible cleat system, under (near) fixed volume versus fixed stress conditions. To isolate the effect of sorption on permeability evolution, helium (non-sorbing gas) was used as a control fluid. All flow-through tests reported here were conducted under conditions of single-phase flow at 40°C, at applied Terzaghi effective confining pressures of 14–41 MPa. Permeability evolution versus effective stress data were obtained under both fixed volume and fixed stress boundary conditions, showing an exponential correlation. Importantly, permeability (κ) obtained at similar Terzaghi effective confining pressures showed κhelium > κCH4 >> κCO2, while κ-values measured in the fixed volume condition were higher than those in the fixed stress case. The results show that permeability to CH4 and CO2, under in situ conditions where free swelling of rock is not possible, is strongly influenced by the coupled effects of 1) self-stress generated by constrained swelling, 2) the change in effective stress coefficient upon sorption, 3) sorption-induced closure of transport paths independently of poroelastic effect, and 4) heterogeneous gas penetration and equilibration, dependent on diffusion. Our results also show that the Walsh permeability model offers a promising basis for relating permeability evolution to in situ stress evolution, using appropriate parameter values corrected for the effects of stress–strain–sorption.